(untitled) (REVUE ROUMAINE DES SCIENCES TECHNIQUES — SÉRIE ÉLECTROTECHNIQUE ET ÉNERGÉTIQUE, 2026)
The concept of the Internet of Things has become increasingly intriguing in recent years. It is foreseeable that in the coming years, systems used in various fields, such as healthcare, agriculture, transportation, and energy, will transition to IoT-based systems. The transition of transformer substations, which hold a crucial position in the power distribution network, to IoT-based applications forms the foundation of this study. In many systems currently in operation, transformer substations are monitored and controlled via SCADA. However, SCADA systems require devices that perform central control and data monitoring functions to use the same communication protocol. In contrast, IoT-based systems enable the use of various devices and do not require additional storage capacity for data. In this study, a model has been developed to monitor and control an IoT-based transformer substation for smart grid applications. The identified transformer parameters were tracked through an IoT-based monitoring system. The obtained data demonstrated the system’s successful operation.